1.6k views
1 vote
Find the missing term (x^12)^5 x (x^-2)^9 x what =(x^40)^5

User Jitender
by
5.3k points

2 Answers

2 votes

Answer:

The missing term is x^158

Explanation:

Let A denote the missing term.


(x^(12))^5 \cdot (x^(-2))^9 \cdot A =(x^(40))^5\\x^(60)\cdot x^(-18)\cdot A = x^(200)\\x^(42)\cdot A = x^(200)\\A = x^(200)\cdot x^(-42)=x^(158)

User Keja
by
5.1k points
3 votes

Answer:


x^(158)

Explanation:

We are given,


(x^(12) )^(5) * (x^(-2) )^(9) * y = (x^(40) )^(5).

It is required to find the value of y.

Now, on simplifying above equation, we get,


x^(60) * x^(-18) * y = x^(200)

i.e.
x^(42) * y = x^(200)

i.e.
y = x^(200) * x^(-42)

i.e.
y = x^(158)

Hence, the missing term is
x^(158).

User Erik J
by
5.8k points